PELAKSANAAN KOORDINASI DINAS PENDIDIKAN DAN SATUAN POLISI PAMONG PRAJA DALAM UPAYA PENERTIBAN PELAJAR DI KOTA PEKANBARU - Lestari, Rahayu; Sahuri, Chalid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Student’s mischief at Pekanbaru City have not handled with every consideration bythe side that relate. In fact, a lot of student in Elementary School (SD), Junior High School(SMP) and Senior High School (SMA) which breached the discipline of School , that Studentcomes out at the moment of hour’s lesson still happened, there is a student that do not go toSchool and more choosed to play at Games Station and billiards. This phenomenon can notcontinually let because Student constitutes Nation Child that becomes State Asset that willdrawn out State accountability to the fore it. The Student is necessarily at School whileeffective hour study be happen, are not on the contrary come out and play Schooledenvironment outboard.In coordination theory by A.F Stooner, available factor which regard coordinationperforming, which is: planning, communication, division task and observation. This researchintent to know coordination performing on duty Education and Unit of Pamong Praja's Policein the effort to controled the Student at Pekanbaru City.Observational model that is utilized in this research is qualitative observational . Withtech that is utilized which is snowball is sampling, to key informan research namely on dutyEducation Department of Pekanbaru City, Unit of Pamong Praja's Police in Pekanbaru City,headmaster, parents, then analyze and process.Base on the research that already being done, with gets guidance on that cognitive conceptperforming at Pekanbaru City, did not optimaly by Education Department and Unit ofPamong Praja's Police Pekanbaru City.Key word: MOU, Coordination,Control, Student